Optical Characterization of Zinc Modified Bismuth Silicate Glasses - Rajesh Parmar; J. Hooda; R. S. Kundu; R. Punia; N. Kishore (International Journal of Optics)
The optical characterization of glass samples in the system 40SiO2 · xZnO · (60-x)Bi2O3 with x=0, 5, 10, 15, 20, 25, 30, 35, and 40 prepared by conventional melt-quench technique has been carried out in the light of Hydrogenic Excitonic Model (HEM). The absorption coefficient spectra show good agreement with theoretical HEM for the present glass system and the values of different parameters like Eg, R, Γ1, Γc, and Co have been estimated from fitting of this model. The values of energy band gap estimated from fitting of HEM with experimental data are in good agreement with those obtained from Tauc’s plot for direct transitions. The band gap energy is found to increase with increase of ZnO content. The decrease in values of Urbach energy with increase in ZnO content indicates a decrease in defect concentration in the glass matrix on addition of ZnO content. Optical constants n and k obey k-k consistency and the dielectric response of the studied glass system is similar to that obtained for Classical Electron Theory of Dielectric Materials. The calculated values of the metallization criterion (M) show that the synthesized glasses may be good candidates for new nonlinear optical materials.